Otimização da Envolvente de Edifícios Antigos numa Perspetiva Energética e de Conforto - Eurico Lima Baptista de Barros (2012)
The national built environment is made by a lot of old buildings that do not provide a thermal comfort according to the current users expectations, who have more demanding requisites. The satisfaction of those who occupy the buildings involves the use of heating and cooling systems that model the internal environment, making it more enjoyable. The current and the future economic context resulting in reduced availability for the use of systems to mitigate the natural handicaps of buildings designed at other times. Thus, with the proclamation of the concept of sustainability, emerged new regulation that encourages rehabilitation and thermal efficiency of the existing buildings. In this dissertation it is intended to understand how to intervene in constructive elements that make up the surroundings of the buildings in order to optimize their thermal comfort taking into account the energy efficiency. The methodology includes the analysis of important publication on this subject, emphasizing the promotion of energy rehabilitation and the buildings, the determination and qualification of the parameters used to evaluate thermal comfort in homes and the identification and characterization of the elements that make up the surroundings of a building that may be subject to interventions to improve their behavior. The evaluation of the influence of each building element on the performance of building as well as the optimization of its external surroundings is made from the sensitivity studies, using a computer program for this, which is applied to a case study including a single-family residential old building typical of Oporto. That computer program is called Pleiades and uses the model calculation called COMFIE, being a space reserved for the description of their functioning. KEYWORDS: Thermal Comfort, Rehabilitation, Surroundings, Buildings, Thermal Quality